Asiaticoside Prevents Oxidative Stress and Apoptosis in Endothelial Cells by Activating ROS-dependent p53/Bcl-2/Caspase-3 Signaling Pathway - Liang, Zhenwen; Chen, Yu; Gu, Rifang; Guo, Qi; Nie, Xuqiang (Current Molecular Medicine, 2023)
Background: Asiaticoside (AC) is a triterpenoid saponin found in Centella asiatica (L.) urban extract that has a wide range of pharmacological properties. Our previous study demonstrated that AC could promote angiogenesis in diabetic wounds, but the specific mechanisms remain unknown. Objective: This study aimed to examine the effectiveness and mechanism of AC on human umbilical vein endothelial cells (HUVECs) exposed to tert-butyl hydroperoxide (t-BHP) toxicity. Methods: Senescence was confirmed using senescence-associated betagalactosidase (SA-β-gal) activity and expression of the cell cycle phase markers p16 and p21. The levels of SOD, NO, MDA, GSH-Px, and ROS were tested. Furthermore, several cell death-related genes and proteins (p53, Bax, Bcl-2 and Caspase-3) were assessed with RT-qPCR and Western blotting. Results: AC significantly reduced SA-β-gal activity, with both the suppression of cellcycle inhibitors p16 and p21. We also found that the induced oxidative stress and apoptosis caused by t-BHP treatment resulted in the decrease of antioxidant enzymes activities, the surge of ROS and MDA, the up-regulation of p53, Bax and caspase-3, and the decrease of SOD, NO, GSH-Px and Bcl-2. These biochemical changes were all reversed by treatment with varying doses of AC. Conclusion: AC alleviates t-BHP-induced oxidative injury and apoptosis in HUVECs through the ROS-dependent p53/Bcl-2/Caspase-3 signaling pathway. It may be a potential antioxidant applied in metabolic disorders and pharmaceutical products.
Keywords: human umbilical vein endothelial cells